Development of An IoT-Based Heart Rate Monitoring System Using Android Application - Achmad Dimyati; Inayatul Inayah; Lis Sa'odah; M. Yusuf (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2025)
Real-time heart rate monitoring plays an important role in early detection of cardiovascular anomalies. However, many existing IoT-based solutions still lack seamless integration of real-time sensing, cloud synchronization, and mobile visualization. This study develops and evaluates an IoT-based heart rate monitoring system using a pulse sensor, Arduino Uno, NodeMCU ESP8266, Firebase real-time database, and an Android application. Experimental testing involving six participants and 60 measurement samples demonstrates that the system achieves a high accuracy of 98.63% compared to a standard fingertip oximeter, with an average error rate of 1.37%, indicating reliable and stable performance. The system supports continuous data acquisition, real-time cloud storage, and mobile access, enabling users to view live and historical heart rate trends through the Android interface. The main contributions of this research include an end-to-end integrated IoT architecture for continuous monitoring, empirical validation of accuracy using a medical-grade comparator, and the provision of time-stamped cloud-based heart rate data for remote health monitoring. These findings confirm the feasibility and significance of IoT–mobile integration as an accessible solution for continuous cardiovascular monitoring.